A CIPP evaluation of the East Kalimantan dual track culinary arts program: Inter-school disparities and outcome convergence - Stevanus Widuri Nursusanto; Putu Sudira; Septian Rahman Hakim; Nuryake Fajaryati; Robertus Vembry Mahartantyo (Jurnal Pendidikan Vokasi, 2025)
Senior high school (SMA) graduates remain the largest contributor to open unemployment in East Kalimantan Province, revealing a structural gap between general secondary education and labor-market demands. The provincial Dual Track Program in Culinary Arts integrates 120 hours of vocational training into the senior high school curriculum to address this challenge. This study provides the first province-wide evaluation of the program using the Context–Input–Process–Product (CIPP) framework. A quantitative cross-sectional census was conducted across all 39 implementing schools, involving 331 students and 52 trainers. Data were collected using content-validated questionnaires with excellent reliability and analyzed using JASP. The results indicate that Process is the strongest predictor of Product outcomes (β = .474), explaining a substantial proportion of variance (R² = .672), while Cohort II achieved significantly better implementation outcomes than Cohort I. Although schools differed significantly in Context, Input, and Process, student Product outcomes remained statistically comparable, suggesting that the program promotes relatively equitable learning outcomes despite disparities in school resources. This study contributes the first multivariate empirical evaluation of the East Kalimantan Dual Track Program and demonstrates the central role of implementation quality in achieving equitable vocational outcomes. The findings provide practical guidance for prioritizing trainer development and mentoring over additional equipment procurement and may inform vocational policy in regions facing similar educational and labor-market challenges.